Architecture and Climate Change : 20 Interviews on the Future of Building - Adeyemi, Kunlé; Ban, Shigeru; Bilbao, Tatiana; Boltshauser, Roger; Braungart, Michael; Buser, Barbara; De Wolf, Catherine; Deurs, Camilla van; Hassell, Richard; Heringer, Anna; Hofmeister, Sandra; Lacol; et al. (DETAIL, 2024)
Architecture and construction are at a turning point. They account for more than 40% of global CO2 emissions. Rising temperatures can only be reduced if there is a radical change in the field of construction throughout the world. However, how should we design our cities, buildings and living spaces so that we can get closer to the goal of decarbonisation? The book gives 20 architects and urban planners their say on the future of construction. Voices are heard from Mexico to Kenya - from Bangladesh to Switzerland. In the interviews experts give an account of their own experiences with climate-friendly construction as well as regional problems posed by rising CO2emissions. They explain pioneering projects and combine them with their personal desire and political ideals.